RIGHT TO HEALTHCARE: A DOCTRINAL STUDY OF COMPULSORY LICENSING OF MEDICINES IN INDIA - K.S. Gopalakrishnan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In today’s world, each one relies on one or more pills to survive and extend their life amid new diseases. Though the advancement of science and technology certainly resulted in numerous changes in society; it has not come up with a panacea to cure the most challenging survival issue which is to combat poverty and disparity. Pharmaceutical companies are like a demi-god and they decide who should live and who not. Patent for R&D to encourage and incentivize creators has, on the other hand, posed a threat to the public in accessing and affording the patented products, especially in the case of medicine and health. The disparity among world nations and the application of one general rule to overcome the situation concerning access the medicine is not a proper solution. However compulsory licensing issued to balance the disadvantages caused by issuing patents has to be analyzed concerning its working. Hence this article would throw light on the use of the compulsory license by the government with special reference to accessing medicines. To analyze the same this paper would extensively discuss the Conceptual viewpoint of compulsory licensing, the phase of the patent in public health, use of the compulsory license by the government with special reference to accessing medicines.